2017
DOI: 10.2298/abs160421108e
|View full text |Cite
|
Sign up to set email alerts
|

Azadirachtin-induced effects on various life history traits and cellular immune reactions of Galleria mellonella (Lepidoptera: Pyralidae)

Abstract: The effects of the botanical insecticide azadirachtin were examined on the life history traits, fecundity and immune parameters of Galleria mellonella L. (Lepidoptera: Pyralidae). We determined that for the topical application of azadirachtin, the LC 50 was 16.564 ppm; at 100 ppm the adult emergence time was prolonged, however the longevity of adults remained unchanged above sublethal concentrations. The mean number of healthy eggs and the fecundity of adults decreased, whereas the number of defective eggs inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 45 publications
(75 reference statements)
9
37
1
1
Order By: Relevance
“…Therefore, the suppression of cell‐mediated immune responses may be associated with the inhibition of eicosanoids synthesis and increasing oxidative stress in BA‐treated larval groups. Our results are in agreement with previous studies which reported similar findings for G. mellonella larvae exposed to various environmental compounds (Altuntaş et al, ; Er et al, ; Mizerska‐Dudka & Andrejko, ). We, therefore, argue that BA treatment suppresses melanization, nodule and capsule formation in larval hemocytes.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Therefore, the suppression of cell‐mediated immune responses may be associated with the inhibition of eicosanoids synthesis and increasing oxidative stress in BA‐treated larval groups. Our results are in agreement with previous studies which reported similar findings for G. mellonella larvae exposed to various environmental compounds (Altuntaş et al, ; Er et al, ; Mizerska‐Dudka & Andrejko, ). We, therefore, argue that BA treatment suppresses melanization, nodule and capsule formation in larval hemocytes.…”
Section: Discussionsupporting
confidence: 94%
“…Arguably, the observed suppression of cell viability in our study is a viable explanation for the decrement in the circulating THC in G. mellonella larvae. Consistent with our findings, recent studies about the effects of several insecticides on the hemocyte numbers of G. mellonella larvae have reported similar findings (Coates et al, 2018;Er et al, 2017;Kurt & Kayis, 2015;Yücel & Kayis, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations